An Evaluation of the EQUIP Treatment Programme with Men who have Intellectual or Other Developmental Disabilities. Issue 2 (28th December 2012) - Langdon, Peter E.; Murphy, Glynis H.; Clare, Isabel C.H.; Palmer, Emma J.; Rees, Joanna
<x xml:space="preserve">Abstract</x> Background The Equipping Youth to Help One Another Programme (EQUIP) was designed for young offenders to address a developmental delay in moral reasoning, distorted cognitions and social skills. Methods The present authors undertook a single case series study and piloted an adapted version of the EQUIP programme with three men with intellectual disabilities and four men with a diagnosis of Asperger Syndrome, all of whom were detained in a medium‐secure forensic unit for people with intellectual disabilities. Treatment was delivered over a 12‐week period, and participants took part in four‐one‐hour sessions per week. Results The results suggested that treatment was successful at increasing moral reasoning ability, reducing distorted cognitions and improving ability to choose effective solutions to problems. However, treatment did not have a significant effect upon anger. Conclusions The EQUIP programme is a promising treatment, but further research is needed to investigate its effectiveness with men with intellectual or other developmental disabilities.